The effect of relative hypotension on 30-day mortality in older people receiving emergency care - Rhiannon Owen (Internal and Emergency Medicine, 2024)
Research has observed increased mortality among older people attending the emergency department (ED) who had systolic pressure > 7 mmHg lower than baseline primary care values. This study aimed to (1) assess feasibility of identifying this ‘relative hypotension’ using readily available ED data, (2) externally validate the 7 mmHg threshold, and (3) refine a threshold for clinically important relative hypotension. A single-centre retrospective cohort study linked year 2019 data for ED attendances by people aged over 64 to hospital discharge vital signs within the previous 18 months. Frailty and comorbidity scores were calculated. Previous discharge (‘baseline’) vital signs were subtracted from initial ED values to give individuals’ relative change. Cox regression analysis compared relative hypotension > 7 mmHg with mean time to mortality censored at 30 days. The relative hypotension threshold was refined using a fully adjusted risk tool formed of logistic regression models. Receiver operating characteristics were compared to NEWS2 models with and without incorporation of relative systolic. 5136 (16%) of 32,548 ED attendances were linkable with recent discharge vital signs. Relative hypotension > 7 mmHg was associated with increased 30-day mortality (HR 1.98; 95% CI 1.66–2.35). The adjusted risk tool (AUC: 0.69; sensitivity: 0.61; specificity: 0.68) estimated each 1 mmHg relative hypotension to increase 30-day mortality by 2% (OR 1.02; 95% CI 1.02–1.02). 30-day mortality prediction was marginally better with NEWS2 (AUC: 0.73; sensitivity: 0.59; specificity: 0.78) and NEWS2 + relative systolic (AUC: 0.74; sensitivity: 0.63; specificity: 0.75). Comparison of ED vital signs with recent discharge observations was feasible for 16% individuals. The association of relative hypotension > 7 mmHg with 30-day mortality was externally validated. Indeed, any relative hypotension appeared to increase risk, but model characteristics were poor. These findings are limited to the context of older people with recent hospital admissions.